Explanation:
(6x^3 + 3x² + 3) + (2x^3 - 5x + 1)
6x^3 + 2x^3 = 8x^3
3x^2 + 0 = 3x^2
-5x + 0 = -5x
3 + 1 = 4
8x^3 + 3x^2 - 5x + 4 is the answer because you have to put all the terms that were solved together. This will lead to 8x^3 + 3x^2 - 5x + 4. And, standard form is ax^2 + bx + c. So, 8x^3 + 3x^2 - 5x + 4 is the answer.
8x^3 + 3x^2 - 5x + 4
Hope this helped,
Kavitha
Answer:
= 8x³ + 3x² - 5x + 4
(6x³ + 3x² + 3) + (2x³ - 5x + 1)
= 6x³ + 3x² + 3 + 2x³ - 5x + 1 remove parentheses
= 6x³ + 2x³ + 3x² - 5x + 1 group like terms
= 8x³ + 3x² - 5x + 3 + 1 add similar elements
5.3m questions
6.9m answers